2022
DOI: 10.1007/s10956-022-09963-2
|View full text |Cite
|
Sign up to set email alerts
|

Location-Based Learning and Its Effect on Students’ Understanding of Newton’s Laws of Motion

Abstract: Location -based learning refers to place-based education conducted online with the use of geographic information systems and mobile devices; with the shift to distance learning, its integration in science education warrants careful evaluation. The goal of this study was to examine the effect of location-based learning on students’ understanding of Newton’s laws of motion and to characterize the learning outcomes. The participants were 373 eighth-grade students, divided into two groups: control ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The researchers went further to say there is no significant difference between achievement of urban and rural located schools taught general science with innovative teaching methods not minding the gender and there is no significance difference in achievement among male and female students taught general science in both school locations using the same innovative teaching method. More so Asakle and Barak [21] asserted that school location determine academic achievement of students taught newton's laws of motion in western Europe but not when taught with innovative teaching methods. The authors opined that urban students taught newton's laws of motion using innovative teaching method achieved better than their rural and semi urban students not minding their gender and innovative teaching method may equally help in improving other students' academic achievement other than urban students.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers went further to say there is no significant difference between achievement of urban and rural located schools taught general science with innovative teaching methods not minding the gender and there is no significance difference in achievement among male and female students taught general science in both school locations using the same innovative teaching method. More so Asakle and Barak [21] asserted that school location determine academic achievement of students taught newton's laws of motion in western Europe but not when taught with innovative teaching methods. The authors opined that urban students taught newton's laws of motion using innovative teaching method achieved better than their rural and semi urban students not minding their gender and innovative teaching method may equally help in improving other students' academic achievement other than urban students.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the related literature, a considerable number of studies are found on students' conceptions in Newtonian mechanics. The main results of these empirical investigations of teaching and learning in mechanics were that students have many misconceptions and few changes in conceptual understanding appear after teaching (Fadaei & Mora, 2015;Bulunuz & Bulunuz, 2016;Ergin, 2016;Liu & Fang, 2016;Wood, Galloway, & Hardy, 2016;Atasoy & Ergin, 2017;Bani-Salameh, 2017;Khandagale, & Chavan, 2017;Handhika, Cari, & Suparmi, 2017;Roemmele & Sederberg, 2017;Erfan & Ratu, 2018;Nie et al, 2019;Topalsan, & Bayram, 2019;Lei & Fritchman, 2021;Asakle & Barak, 2022;Baring & Berame, 2022). On the other hand, in this study, it has been shown by using the tracker program that the coin representation (and similar examples) used in many studies in teaching Newton's First Law are not suitable examples for the first law.…”
Section: Introductionmentioning
confidence: 99%